2003
DOI: 10.1177/076737010301800203
|View full text |Cite
|
Sign up to set email alerts
|

Approche empirique de l'immersion dans l'expérience de consommation: les opérations d'appropriation

Abstract: Selon tout un courant de recherche, le consommateur cherche à s'immerger dans des expériences de consommation plutôt qu'à simplement rencontrer des produits finis. Cependant, ce phénomène d'immersion et le moyen d'y accéder ont fait l'objet de peu de recherches empiriques en marketing. À partir d'une revue de l'état de l'art en marketing, le cadre conceptuel de l'appropriation est introduit et développé pour rendre compte des opérations subjectives menées par le consommateur pour accéder à l'immersion. Une ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
57

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(106 citation statements)
references
References 46 publications
(36 reference statements)
2
47
0
57
Order By: Relevance
“…The different socio-historical developments have transformed consumption patterns, and contrary to the trend of material consumption that existed before, we now consume to produce social identity or experience, with an appeal for the intangible (Rochefort, 1995). In our post-modern society, consumer society changed attitudes towards leisure: Consumption is cherished and considered an experience-rewarding to consumers looking for hedonism in their purchases (Caru & Cova, 2003;Filser, 2002;Holbrook & Hirschman, 1982). Thus, hedonism and the growing maturity of consumers who are becoming increasingly demanding and selective make the task even more difficult for retailers.…”
Section: Introductionmentioning
confidence: 99%
“…The different socio-historical developments have transformed consumption patterns, and contrary to the trend of material consumption that existed before, we now consume to produce social identity or experience, with an appeal for the intangible (Rochefort, 1995). In our post-modern society, consumer society changed attitudes towards leisure: Consumption is cherished and considered an experience-rewarding to consumers looking for hedonism in their purchases (Caru & Cova, 2003;Filser, 2002;Holbrook & Hirschman, 1982). Thus, hedonism and the growing maturity of consumers who are becoming increasingly demanding and selective make the task even more difficult for retailers.…”
Section: Introductionmentioning
confidence: 99%
“…The process through which consumers interact with a product, gaining access to a holistic experience, is called 'customer immersion' [Arnould et al, 2002;Gilmore, 1998, 1999;Schmitt, 1999], but little is known about it. In order to delve deeper into the topic of experiential marketing, Carù and Cova [2003] have researched the cultural sector, exploring in particular the consumption experience during a classical music concert. Referring to the processes of spatial appropriation, the two authors have identified the sequential stages making up the immersion process, considering that by reducing the perceived distance between individuals and the object they are experiencing (classical music in the specific instance), customer immersion increases, with a consequent rise in value for the consumer.…”
Section: Attitude Toward the Shop: Disloyalty (Fnac) Versus Loyalty (mentioning
confidence: 99%
“…The more a customer project himself in a buying or consumption experience the more he's likely to experience impulses buying (Hoch & Loewenstein, 1991;Ortony et al, 1990). The projection of an individual would not come true only if he will arrive to appropriate the retail outlet and immerse in a consumption experience (Filser, 2002;Carù & Cova, 2003. Thus we propose the hypothesis H1: The concept of in-store lived experience has a positive influence on impulses buying.…”
Section: Predictive Validitymentioning
confidence: 99%
“…Carù and Cova (2003) talk about immersion as a way to access to the experience. They emphasize the concept of appropriation (of space or the experience) as a prerequisite for the immersion.…”
Section: Experiential Dimensionmentioning
confidence: 99%
See 1 more Smart Citation